National Museum of African American History and Culture: A Museum 100 Years in the Making - Beer, Sarah J. (My University, 2017)
The Smithsonian Institution has been making headlines in recent news for one momentous reason: the opening of a new museum commemorating African American history. Beginning in 1916, several bills, resolutions, and hearings have taken place in Congress to introduce legislation that would create a museum, but none would be successful. John Lewis picked up the fight by introducing legislation immediately after becoming a Georgia congressman in 1986. It took Lewis almost twenty years, but in 2003 President George W. Bush finally signed the law to create the National Museum of African American History and Culture. My capstone paper studies the congressional history, early reviews, and content of the museum while also including my personal review: as a public history student, I pay close attention to how the museum presents the content and narrative, as well as the content and narrative themselves. I am able to do this because a research grant through the Office of Research and Sponsored Programs gave me the opportunity to visit the museum in early November. Through this experience I found the museum to be overwhelming and lacking in organization and logical layout, though it does offer the visitor glimpses at priceless pieces of history and a unique narrative. The stories in the museum are important to tell because they help confront a somber history that is inextricably tied to the American experience. But the story of NMAAHC is also important to tell because those involved have overcome every possible obstacle to bring these stories to us.
Series: USGZE AS333
Keywords: African American--History.; National Museum of African American History and Culture (U.S.)